2009
DOI: 10.1007/s11259-009-9313-5
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin and aminoglycoside resistance in Staphylococcus aureus isolates from bovine mastitis and sequence analysis of their mecA genes

Abstract: Although methicillin-resistant Staphylococcus aureus (MRSA) were generally isolated from human beings; these agents were recently isolated from various animal species. It has been shown that MRSA isolates are not only resistant to beta-lactam antibiotics, but can also be resistant to the other commonly used antibiotics. In this study, 18 phenotypic methicillin resistant S. aureus isolates from bovine mastitis cases were analyzed by PCR for the presence of mecA gene encoding methicillin resistance and aac (6′)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 38 publications
7
33
1
1
Order By: Relevance
“…The same results were also stated for the presence of mecA genes from bovine mastitis (Turutoglu et al, 2009 andVishnupuriya et al, 2014) dogs, cats (Malik et al, 2006) and horses (Schnellmann et al, 2006). Based on the results from the present study and the other studies (vanDuijkeren et al, 2004 andMalik et al, 2006), it can be construed that these isolates might have originally come from humans, considering that the methicillin resistance among human Staphylococcus isolates is common.…”
Section: Sequencing and Phylogenetic Analysis Of Mrsa Isolatessupporting
confidence: 87%
See 1 more Smart Citation
“…The same results were also stated for the presence of mecA genes from bovine mastitis (Turutoglu et al, 2009 andVishnupuriya et al, 2014) dogs, cats (Malik et al, 2006) and horses (Schnellmann et al, 2006). Based on the results from the present study and the other studies (vanDuijkeren et al, 2004 andMalik et al, 2006), it can be construed that these isolates might have originally come from humans, considering that the methicillin resistance among human Staphylococcus isolates is common.…”
Section: Sequencing and Phylogenetic Analysis Of Mrsa Isolatessupporting
confidence: 87%
“…The possible reasons for this type of discrepancy are that the isolates appeared to show poor expression of mecA genes or production of methicillinase (alteration of PBP subtypes) or seem to overproducing β-lactamase. The phenotypic expression of resistance could vary due to growth conditions which are also involved in the expression of methicillin resistance (Zmantar et al, 2008;Turutoglu et al, 2009 andTurkylmaz et al, 2010).…”
Section: Genotypic Identification Of Mrsa Isolatesmentioning
confidence: 99%
“…On the contrary, de Oliveira et al [45] found that overall level of resistance was generally low to all antimicrobial agents that are currently commercially available to treat bovine mastitis. [18,46,47] . In this study, 100% of isolates of S. aureus and CNS were methicillin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, a few studies have reported the occurrence of MRSA from bovine mastitis and proportion of resisting isolates was low [18,46,47] . In this study, 100% of isolates of S. aureus and CNS were methicillin-resistant.…”
Section: Saidi Canteki̇n Khelef Ergün Solmaz Kaidimentioning
confidence: 99%
See 1 more Smart Citation